Alignment : using the balanced scorecard to create corporate synergies - Kaplan, Robert S.; Norton, David P., 1941- (Boston, Mass. : Harvard Business School Press, 2006)
"Most organizations contain multiple business and support units, each led by highly trained, experienced executives and staffed by talented employees. But too often, different units fail to coordinate: they work at cross-purposes and have conflicting goals. Results? Performance-sapping disagreements, lost opportunities, wasted resources - and a corporation whose value amounts to less than the sum of its parts." "Robert S. Kaplan and David P. Norton explain how to correct such organizational misalignment - not only within a company but between the firm and its board of directors, investors, customers, and suppliers."
"The authors maintain that the responsibility for organizational alignment lies with corporate headquarters. They show how top executives can build a corporate-level strategy map and scorecard that graphically depict their company's "enterprise value proposition"--How the organization creates synergies from its business units - and use the revolutionary Balanced Scorecard management system to set, coordinate, and oversee implementation of high-level strategy."--Jacket.
Alignment : a source of economic value -- Corporate strategy and structure : historical perspective -- Aligning financial and customer strategies -- Aligning internal process and learning and growth strategies : integrated strategic themes -- Aligning support functions -- Cascading : the process -- Aligning boards and investors -- Aligning external partners -- Managing the alignment process -- Total strategic alignment.
Includes bibliographical references and index.
Print version record.
OCLC control number change
Keywords: Strategic planning; Industrial management; Industrial organization; Strategic alliances (Business); Organizational effectiveness; Planification stratégique; Gestion d'entreprise.; Industrie -- Organisation, contrôle, etc; Alliances stratégiques (Affaires); Efficacité organisationnelle; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Industrial management; Industrial organization; Organizational effectiveness; Strategic alliances (Business); Strategic planning; Balanced Scorecard; Strategische Planung; Unternehmenskooperation; Unternehmensplanung; Strategische planning; Samenwerkingsvormen (bedrijfseconomie); Effectiviteit; Interne organisatie; Planification stratégique; Alliances stratégiques (affaires); Tableaux de bord (gestion); Sujet -- Forme -- Géographique -- Chronologique; elektronické knihy; electronic books